Hubungan Pengetahuan Ibu Bekerja Dengan Tumbuh Kembang Balita Di Klinik Kasih Ibu Sejati, Kelurahan Sei Sikambing C II, Kecamatan Medan Helvetia - Dealita Khairani Daulay (STIKES Columbia Asia Medan, 2025)
The toddler period is a golden stage of child development influenced by several factors, including maternal knowledge in parenting. Working mothers face challenges in balancing professional responsibilities with caregiving roles. This study aimed to examine the relationship between working mothers’ knowledge and the growth and development of toddlers at Kasih Ibu Sejati Clinic, Sosa District, Padang Lawas Regency. This research used a descriptive analytic design with a cross-sectional approach involving 42 working mothers with toddlers. The results showed that most working mothers had good knowledge (38.1%) and most toddlers were in the good developmental category (64.3%). The Chi-square test yielded a p-value of 0.004, indicating a significant relationship between the mother's level of knowledge and toddler development. Good knowledge enables mothers to provide better-quality care despite time limitations. These findings imply the importance of enhancing education for working mothers to support optimal child development.